a PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) PADA MATA PELAJARAN IPAS TERHADAP KREATIVITAS BELAJAR SISWA KELAS IV DI SD GMIT OEBOBO - Isu, Yishariana Lidyati; Heryon Bernard Mbuik; Yulsy Marselina Nitte (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Isu, Yishariana. (2026). The Effect of the Project Based Learning (PjBL) Model in Science and Social Studies (IPAS) on the Learning Creativity of Fourth Grade Students at SD GMIT Oebobo. Supervised by Heryon Bernard Mbuik, S.PAK., M.Pd. and Yulsy Marselina Nitte, S.H., M.Pd. as First and Second Supervisors. Undergraduate Program in Elementary School Teacher Education, Faculty of Teacher Training and Education, Universitas Citra Bangsa Kupang. This study was motivated by the low level of learning creativity among fourth-grade students in the Science and Social Studies (IPAS) subject, particularly on the topic of energy transformation systems. This issue was primarily caused by the learning process, which was still dominated by the lecture method. The study aimed to determine the level of students' learning creativity before and after the implementation of the Project Based Learning (PjBL) model and to examine the significant effect of this learning model on the learning creativity of fourth-grade students at SD GMIT Oebobo. This study employed a quantitative approach using a pre-experimental research design, specifically the One-Group Pretest-Posttest Design. The sample consisted of all 24 fourth-grade students at SD GMIT Oebobo, selected through total sampling. Data were collected using pretest and posttest instruments, observation sheets to assess learning activities, and a product assessment rubric. The data were analyzed using descriptive statistics and inferential statistics through the Paired Sample t-Test. The results showed a significant improvement in students' learning creativity after the implementation of the Project Based Learning model. The mean score increased from 48.54 in the pretest to 77.92 in the posttest. In addition, the assessment of the students' mini electric fan project yielded an average score of 94.5, which was categorized as highly creative. The hypothesis testing result revealed a significance value (Sig. 2-tailed) of 0.000, which was lower than the significance level of 0.05 (0.000 < 0.05). Therefore, the null hypothesis (H₀) was rejected, and the alternative hypothesis (H₁) was accepted. It can be concluded that the implementation of the Project Based Learning (PjBL) model had a significant effect on the learning creativity of fourth-grade students in the Science and Social Studies (IPAS) subject at SD GMIT Oebobo.